Novel thiazolo[3,2-b]-1,2,4-triazoles derived from naproxen with analgesic/anti-inflammatory properties: Synthesis, biological evaluation and molecular modeling studies - Sarıgöl, Deniz; Baran, Ayşe Uzgören; Tel, Banu Cahide; Kazkayası, İnci; Somuncuoğlu, Elif İnci; Okay, Gürol (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
3-Substituted-1,2,4-triazole-5-thiones are versatile synthetic intermediates for the preparation of several biologically active N-bridged heterocyclic compounds, given that they have two reactive sites, thiocarbonyl and an amine nitrogen (N-1/N-4). For several years, our interest has focused on the synthesis of novel heterocyclic systems derived from 3-substituted-1,2,4-triazole-5-thiones having analgesic/anti-inflammatory activity. In this study, a series of novel thiazolo[3,2-b]-1,2,4-triazole-6(5H)-one derivatives bearing naproxen was synthesized and evaluated for their in vivo analgesic and anti-inflammatory properties in acute experimental pain and inflammation models. The compounds were also tested for their ulcerogenic potential. Our findings showed that all the newly synthesized derivatives attenuate nociception and inflammation compared with a control. All the synthesized compounds exhibited much lower ulcerogenic risk than the standard drugs indomethacin and naproxen. Some compounds with significant analgesic and/or anti-inflammatory activities as well as low ulcer scores were further evaluated for in vitro COX-1 and COX-2 inhibitory potential in a COX-catalyzed prostaglandin biosynthesis assay. Among the tested compounds, compound 1q showed the highest selectivity index (SI) of 4.87. The binding mode for some of the tested compounds to the cyclooxygenase (COX) enzymes was predicted using docking studies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Naproxen derivatives; Thiazolo[3,2-b]-1,2,4-triazole; Analgesic/anti-inflammatory activity; Ulcerogenic risk; Molecular modeling